The Timeout in Sports: A Study of Its Effect on Volleyball - Fernández-Echeverría, Carmen; González-Silva, Jara; Castro, Inma T.; Perla Moreno, M. (Frontiers in Psychology, 2019)
The purpose of this study was to analyse the variables (lost rallies and score difference) that determine the timeout effect (positive or no effect) in volleyball, in balanced and unbalanced sets. 232 timeouts, requested by the coaches of 66 male and female teams participating in the Spanish Championship in the Under-14 and Under-16 categories, were analysed. The variables considered in this study were timeout effects, lost rallies and score differences. To analyse the timeout effect, a binary logistic regression model was applied. The results of this model show that, in balanced sets, the variables that predict the timeout effect are the number of rallies (≤ 2 lost rallies) and the score difference (2-3 points), whilst in unbalanced sets, the variable that predicts the timeout effect is the number of lost rallies (3 lost rallies). These results show the importance of bearing these variables in mind when timeouts are managed and requested by coaches, in order to optimise the team’s performance.